2006
DOI: 10.1007/s10886-005-9026-3
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylfuran-Lactone Pheromone from Males of Galerucella calmariensis and Galerucella pusilla

Abstract: Male Galerucella calmariensis and Galerucella pusilla (Coleoptera: Chrysomelidae) emit an aggregation pheromone while feeding on host foliage. Isolation of the compound from collected volatiles was guided by comparisons of gas chromatograms of extracts from males and females and by gas chromatography-electroantennographic detection. The compound was identified by a combination of spectrometric methods and microchemical tests as the novel dimethylfuran lactone, 12,13-dimethyl-5,14-dioxabicyclo[9.2.1]tetradeca-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 32 publications
2
30
0
Order By: Relevance
“…Thus, natural products bearing the tetraalkyl-substituted furan ring are relatively unstable, which is a possible reason why the tetraalkyl-substituted furan ring has rarely been found in nature. Recently, a macrolactone bearing a tetraalkyl-substituted furan ring was identified as the aggregation pheromone of leaf beetle (37) and, to the best our knowledge, this is the only example of a tetraalkyl furan ring in a natural product except for F-acids. Moreover, the activity of the green-lipped mussel is known to disappear in aqueous solution.…”
Section: Resultsmentioning
confidence: 96%
“…Thus, natural products bearing the tetraalkyl-substituted furan ring are relatively unstable, which is a possible reason why the tetraalkyl-substituted furan ring has rarely been found in nature. Recently, a macrolactone bearing a tetraalkyl-substituted furan ring was identified as the aggregation pheromone of leaf beetle (37) and, to the best our knowledge, this is the only example of a tetraalkyl furan ring in a natural product except for F-acids. Moreover, the activity of the green-lipped mussel is known to disappear in aqueous solution.…”
Section: Resultsmentioning
confidence: 96%
“…In most cases, however, the synthetic pheromone compounds alone are only weakly attractive (Cossé et al, 2002;Dickens et al, 2002;Rao et al, 2003;Soroka et al, 2005;Tóth et al, 2005;Bartelt et al, 2006;. Peng and Weiss (1992) first provided evidence for a male-produced aggregation pheromone in P. cruciferae, and subsequently six male-specific sesquiterpenes were identified, four of which have been synthesized (Bartelt et al, 2001Muto et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, the dispersal ability of G. pusilla was not investigated. Bartelt et al (2006) reported that male G. calmariensis and G. pusilla produce the same aggregation pheromone and is attractive to both species and both sexes. Atkinson and Shorrocks (1981) developed a model to help explain the coexistence of Drosophila spp.…”
Section: Adult and Larval Feedingmentioning
confidence: 99%
“…However, in Oregon G. pusilla was reported to be more abundant than G. calmariensis (Schooler, 1998). Also, at two sites near Chicago, Illinois based on pheromone trapping one site is dominated by G. calmariensis (76%) and the other site by G. pusilla (88%) (Bartelt et al, 2006). McAvoy et al (1997) reported both species present 3 years after release in Virginia.…”
Section: Adult and Larval Feedingmentioning
confidence: 99%
See 1 more Smart Citation